DAYA SAING EKSPOR KOPI ROBUSTA INDONESIA DI PASAR INTERNASIONAL - Ariel Hidayat; Soetriono Soetriono (University of Jember, 2010)
Robusta Coffee is one of mainstay commodity that have strategic support in national economic. Supporting of Robusta Coffee has been faded since 2000, especially after world’s coffee had been crisis cause of over production in the world. Currently, Indonesian coffee activities is getting some problem, such as volume and unstable value of national robusta coffee, compare than other coffee producer countries and also grade of Indonesian coffee is lower quality for export. Research methods were used descriptive and comparative. Analysis were used Revealed Comparative Advantages (RCA), Acceleration Ratio (AR) and Index of Trade Specialization (ISP) and Sensitivities. This research has aimed to know comparative advantages, export activities, position and competitiveness also robusta coffee sensitivities when world coffee price changing. The results of the research showed (1) Indonesia has robusta coffee comparative advantages. (2) Indonesia is able to achieve robusta coffee market during 2004 till 2006. (3) Indonesia has high competitiveness or domestic supply more bigger than domestic demand and Indonesia placed in maturity stage. (4) Rising of robusta coffee price from 5%, 10% and 20%, increasing comparative advantages, increasing export activities, and competitiveness of robusta coffee is constant. If robusta coffee price decrease from 5%, 10% and 20%, it will decrease comparative advantages and export activities also competitiveness of robusta coffee is stable.Keywords: Competitiveness, Comparative Advantages, Export Activities, Sensitivities